2018
DOI: 10.24105/apr.2018.5.15
|View full text |Cite
|
Sign up to set email alerts
|

The impact of fluorescent and led lighting on students attitudes and behavior in the classroom

Abstract: Introduction: This study examined empirical research on the effects of high correlated color temperature light-emitting diodes (LED) and fluorescent lighting on students in the classroom. LED is becoming the most recent lighting option for optimal energy efficiency over fluorescent technology. Background: A review of the literature indicates correlated color temperature (CCT) of lighting has nonvisual effects on students, with higher CCT positively impacting attitudes and behavior. The review also revealed cur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(19 citation statements)
references
References 20 publications
1
14
0
2
Order By: Relevance
“…Scholars (e.g. Hansen, Nielsen, Georgieva & Schledermann, 2017;Hayat, 2017;Morrow & Kanakri, 2018;Nepal & Maharjan, 2015;Wadhwa, 2016) have examined the effect of university/ school utilities quality. For instance, Hansen et al (2017) revealed that appropriate light in the school increased student concentration and promoted pro-social behaviour hence student engagement.…”
Section: Universities Utilities Quality and Student Engagementmentioning
confidence: 99%
“…Scholars (e.g. Hansen, Nielsen, Georgieva & Schledermann, 2017;Hayat, 2017;Morrow & Kanakri, 2018;Nepal & Maharjan, 2015;Wadhwa, 2016) have examined the effect of university/ school utilities quality. For instance, Hansen et al (2017) revealed that appropriate light in the school increased student concentration and promoted pro-social behaviour hence student engagement.…”
Section: Universities Utilities Quality and Student Engagementmentioning
confidence: 99%
“…Приблизно після 2000 р., коли освітлювальна громада познайомилася з фундаментальними механізмами невізуальних біологічних ефектів, набагато більше вивчено у відношенні показників і шкільного освітлення [12][13][14][15][16][17][18][19][20]. Експериментальні умови цих досліджень відрізняються суттєво в локаціях на землі; дизайном вікон в будівлях; порою року (і, таким чином, впливом денного світла) і таймингом експериментів.…”
Section: виклад основного матеріалуunclassified
“…Одне дослідження показало ефект освітлення на основі бажаної активності і настрою [20]. Дослідження показало, що такий освітлення в дійсності позитивно впливає на навчання і настрій студентів.…”
Section: виклад основного матеріалуunclassified
“…In spite of adequacy of lighting in the classroom, it was also found to cause discomfort for students due to light glare on some essential components of classroom furniture, such as desks and whiteboards (Winterbottom & Wilkins, 2009). An emphasis was also placed on the presence of lighting control panel inside the classroom because of its positive effect on student engagement and mood during the school day (Morrow & Kanakri, 2018).…”
Section: Lightingmentioning
confidence: 99%
“…White color Growth (Cheryan et al, 2014;Drabble, 2016;Morrow & Kanakri, 2018;Ott, 1976 (Adewole & Olorunnisola, 2010;Frumkin et al, 2006;Homrighaus et al, 2012;Richards-Babb et al, 2010;Senda, 2015…”
Section: Lightingmentioning
confidence: 99%